Meningkatkan Kompetensi Guru PPG di Indonesia dalam Penulisan Artikel Ilmiah Melalui Pendampingan Berbasis Penelitian Kelas - Yojana, Ratna Mira; Dewayana, Triwulandari Satitidjati; Harahap, Elfira Febriani; Surjasa, Dadang; Mayusda, Idriwal; Lazuardy, Meisya Azka; Veronika, Chica Juliana (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2026)
The Teacher Professional Education Program (PPG) establishes scientific publication as an essential requirement for graduation and teacher professional development. However, a limited understanding of writing scientific articles based on classroom research remains a significant challenge for PPG participating teachers. This Community Service (PkM) activity aims to enhance the writing competency of PPG participating teachers in scientific articles based on classroom research through intensive mentoring. The implementation method consists of the presentation of applied material and personal mentoring in drafting scientific articles. The activity involved 43 PPG participating teachers from various regions in Indonesia. The mentoring was conducted over one month, encompassing the entire writing process, from initial drafting to final revision of the article. The success of the activity was demonstrated by an average post-test score of 95.54% and the output of three draft scientific articles suitable for publication. These results indicate that the mentoring model is efficacious in improving the scientific writing skills of PPG participating teachers and supporting improvements in the quality of education. Keywords: Mentorship, Professional Teacher Education (PPG), Scientific Article, Classroom Research. Program Pendidikan Profesi Guru (PPG) menetapkan publikasi ilmiah sebagai salah satu syarat penting untuk kelulusan dan pengembangan profesional guru. Namun, keterbatasan pemahaman mengenai penulisan artikel ilmiah berbasis penelitian kelas masih menjadi tantangan utama bagi guru peserta PPG. Kegiatan Pengabdian kepada Masyarakat (PkM) ini bertujuan untuk meningkatkan kompetensi guru peserta PPG dalam menulis artikel ilmiah berbasis penelitian kelas melalui pendampingan intensif. Metode pelaksanaan terdiri atas pemaparan materi aplikatif dan pendampingan personal dalam penyusunan draf artikel ilmiah. Peserta kegiatan berjumlah 43 guru peserta PPG yang berasal dari berbagai wilayah di Indonesia. Pendampingan dilaksanakan selama satu bulan, mencakup proses penulisan hingga perbaikan akhir artikel. Keberhasilan kegiatan ditunjukkan oleh nilai rata-rata post-test sebesar 95,54% serta luaran berupa tiga draf artikel ilmiah yang layak dipublikasikan. Hasil ini menunjukkan bahwa model pendampingan efektif dalam meningkatkan kemampuan menulis ilmiah guru peserta PPG dan mendukung peningkatan kualitas pendidikan. Kata Kunci: Pendampingan, Pendidikan Profesi Guru (PPG), Artikel Ilmiah, Penelitian Kelas